Oblikoslovna raznolikost v sevniško-krškem govoru glede na (ne)mestno okolje - Zemljak Jontes, Melita (Jezikoslovni zapiski, 2013)
The local dialect of larger towns or cities tends to be between dialect and standard due to various reasons. This paper presents differences in the use of noun endings in all three genders contrasted with the standard Slovenian word-formation paradigms, also taking into account the urban environment of three selected regional centers and the non-urban countryside of the Sevnica-Krško dialect of the Lower Sava Valley as a part of the Styrian dialect group. The analysis shows that standard or at least less dialect-like endings are relatively rare in the urban environment and thus variation in noun endings is not a systematic differential feature for the urban versus non-urban environment.
Keywords: dialectology; dialektologija; non-urban environment; noun endings; samostalniške končnice; Sevnica-Krško dialect; sevniško-krški govor; Slovene; Slovene langauge; slovenščina